2000
DOI: 10.3171/foc.2000.8.5.6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of big endothelin–1 concentrations in serum and ventricular cerebrospinal fluid after early surgical compared with nonsurgical management of ruptured intracranial aneurysms

Abstract: Object Whereas the removal of subarachnoid blood is possible during early-stage aneurysm surgery, this cannot be achieved in aneurysms treated by endovascular means. The levels of potential spasmogens in the cerebrospinal fluid (CSF) in patients receiving endovascular treatment might therefore be higher, with the potential for more severe post–subarachnoid hemorrhage (SAH) vasospasm. Methods Serum and CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…In aSAH patients, increase in CSF and plasma ET-1 is observed 24 hours from ictus (Kobayashi et al , 1995), and is associated with the occurrence of delayed vasospasm (Gruber et al , 2000a). Animal studies indicate that the increase in cerebral ET-1 after aSAH results from excessive release by astrocytes during the period of initial ischemia (Pluta et al , 1997a).…”
Section: Early Events After Asahmentioning
confidence: 99%
“…In aSAH patients, increase in CSF and plasma ET-1 is observed 24 hours from ictus (Kobayashi et al , 1995), and is associated with the occurrence of delayed vasospasm (Gruber et al , 2000a). Animal studies indicate that the increase in cerebral ET-1 after aSAH results from excessive release by astrocytes during the period of initial ischemia (Pluta et al , 1997a).…”
Section: Early Events After Asahmentioning
confidence: 99%
“…Patients with aSAH were found to have statistically significant elevations of sTNFR-1 in CSF when compared to patients with non-hemorrhagic hydrocephalus, and this elevation correlated with admission Hunt and Hess grade and neurologic outcome as measured by GOS [105]. In our own prospective study evaluating proteomic biomarkers in CSF of patients with aSAH, we found that mean and maximum CSF levels of sTNFR-1 had statistically significant correlation with clinical outcome, with elevated sTNFR-1 levels correlating with poor outcomes as measured by mRS [106].…”
Section: The Role Of Precision Medicine - Biomarkers – Mechanismsmentioning
confidence: 99%
“…Their elevation in serum, CSF, and microdialysis fluid is related to early and delayed ischemia and poor outcome [44, 57]. …”
Section: Early Brain Injurymentioning
confidence: 99%
“…Apoptosis is triggered by elevated ICP, ischemia, reperfusion, and acute vasospasm and by the neurotoxicity of blood breakdown components and oxidative stress [11, 44]. It involves neuronal, glial [87], and smooth muscle and endothelial cells, causing BBB disruption [88] and promoting vasospasm development.…”
Section: Early Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation